Knowledgeable Bankers? The Demand for Research in World Bank Operations - Ravallion, Martin (2012)
Development impact calls for knowledgeable development practitioners. How then do the operational staff of the largest development agency value and use its research? Is there an incentive to learn and does it translate into useful knowledge? A new survey reveals that the bulk of the World Bank's senior staff value the Bank's research for their work, and most come to know it well, although a sizable minority have difficulty accessing research to serve their needs. Another group sees little value to research for their work and does not bother to find out about it. Higher perceived value is reflected in greater knowledge about research, though there are frictions in this process. Staff working on poverty, human development and economic policy tend to value and use research more than staff in the more traditional sectors of Bank lending -- agriculture and rural development, energy and mining, transport and urban development; the latter sectors account for 45 percent of lending but only 15 percent of staff highly familiar with Bank research. Without stronger incentives for learning and more relevant and accessible research products, it appears likely that this lag in demand for research by the traditional sectors will persist.